Home range and migration of the Red-breasted Goose Branta ruficollis mapped by satellite telemetry: implications for conservation - Todorov, Emil; Chisamera, Gabriel B.; Gavril, Viorel D.; Vasiliu, Oana C.; Murariu, Dumitru; Cobzaru, Ioana (Wildfowl, 2024)
The Red-breasted Goose Branta ruficollis, classified as Vulnerable by the IUCN Red List of threatened species, is a long-distance migrant which breeds on the Yamal, Gydan and Taymyr Peninsulas of the Russian arctic. Understanding the birds’ breeding ecology and behaviour during migration can contribute to their efficient conservation. In this study, we fitted two male geese with 18 g Argos Solar PTTs and one female with a 9.5 g Solar PTT to provide information about their breeding home range, time spent in key stopover and staging sites, and the duration of migration. One male and one female goose completed one full cycle of migration, breeding in Taymyr Peninsula and returning to their wintering grounds in southeast Romania. The pre-nuptial migration of the male goose was longer in duration and distance than the post-nuptial migration, which was much shorter. The female goose had shorter pre- and post-nuptial migration than the male. Both geese made more stops during spring than autumn which may be explained by a combination of capital breeding (so stopping more frequently to gain energy reserves in preparation for breeding) and arriving in areas yet to thaw during northbound migration. The summer season in the Taymyr Peninsula lasted roughly 85 days. The male goose bred on a small tributary of the Pyasina River, with a core home range of 20 km2. The female goose had a smaller home range, of 6 km2 in the vicinity of the Rarikha River, near the Gulf of Yenisey. Results of this study provide important knowledge about the birds’ home range, days spent at stopover and staging areas and the distance between those sites. These findings can support conservation communities throughout the species’ range in enabling them to carry out essential conservation activities more effectively.